Detection of giardia duodenalis antigen in human fecal eluates by enzyme-linked immunosorbent assay using polyclonal antibodies (2002)
The present study developed and standardized an enzime-linked immunosorbent assay (ELISA) to detect Giardia antigen in feces using rabbit polyclonal antibodies. Giardia cysts were purified from human fecal samples by sucrose and percoll gradients. Gerbils (Meriones unguiculatus) were infected to obtain trophozoites. Rabbits were inoculated with either cyst or trophozoite antigens of 14 Colombian Giardia isolates to develop antibodies against the respective stages. The IgG anti-Giardia were purified by sequential caprylic acid and ammonium sulfate precipitation. A portion of these polyclonal antibodies was linked to alkaline phosphatase (conjugate). One hundred and ninety six samples of human feces, from different patients, were tested by parasitologic diagnosis: 69 were positive for Giardia cysts, 56 had no Giardia parasites, and 71 revealed parasites other than Giardia. The optimal concentration of polyclonal antibodies for antigen capture was 40 µg/ml and the optimal conjugate dilution was 1:100. The absorbance cut-off value was 0.24. The parameters of the ELISA test for Giardia antigen detection were: sensitivity, 100% (95% CI: 93.4-100%); specificity, 95% (95% CI: 88.6-97.6%); positive predictive value, 91% (95% CI: 81.4-95.9%); and negative predictive value, 100% (95% CI: 96.1-100%). This ELISA will improve the diagnosis of Giardia infections in Colombia and will be useful in following patients after treatment.